Blue rubber bleb nevus syndrome: case report - Teixeira,Magaly Gemio (2003)
The case of a patient with blue rubber bleb nevus syndrome who is infected by acquired immunodeficiency syndrome virus due to multiple blood transfusions is presented. This case shows that although it is a rare systemic disorder, blue rubber bleb nevus syndrome has to be considered in the differential diagnosis of chronic anemia or gastrointestinal bleeding. Patients should be investigated by endoscopy, which is the most reliable method for detecting these lesions. The patient underwent gastroscopy and enteroscopy via enterotomy with identification of all lesions. Minimal resection of the larger lesions and string-purse suture of the smaller ones involving all the layers of the intestine were performed. The string-purse suture of the lesions detected by enteroscopy proved to be an effective technique for handling these lesions, avoiding extensive intestinal resection and stopping the bleeding. Effective management of these patients demands aggressive treatment and should be initiated as soon as possible to avoid risks involved in blood transfusions, as occurred in this case.